Synchronization of oestrus on the sheep with «Prostin» on the oestrus and anoestrus période - ΒΛΑΧΟΣ, Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
During the years 1977 and 1978 it was made synchronization of oestrus on 3 flocks (A.B.C.) of 315 nativ ewes belonging to 3 farmers in two villages situated 20-40 km from Thessaloniki. In all ewes it was injected PMSG (700 IU) and after 6 days it was made the first injection of «Prostin» (PGF2a) 16 mg and after other 7 days the second injection of «Prostin»9. From the 315 ewes the 150 belong to flock A, 115 to flock Β and 50 ewes to flock C. The ewes of flock A and Β were at the beginning of the oestrus période (15% in heat). The ewes of the flock C living in a mountainous country were in anoestrus période. Results: 1) Flock A: conception rate 100%. Number of lambs born 200, twinity 28%, triplicity 2,7%, c?80 9120. 2) Flock B: conception rate 100%. Lambs born 142, twinity 16,5%, triplicity 3,5%, ç?70 972. 3) Flock C: conception rate 6%, lambs born 5, twinity 4%, ^ 3 , 92. Conclusion: from this experiment is to conclude that: 1) The results of synchronization oestrus by using the «Prostin» are good if the treatment is applied after the beginning of the oestrus période. 2) For the stimulation of the ovary it is useful to inject 700 IU PMSG 4-6 days before the prostaglan dins. 3) The results are poor if the treatment is made in the anoestrus période.